2020
DOI: 10.21203/rs.3.rs-22995/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in articular cartilage T2 star relaxation time following mechanical disorders: in vivo canine supraspinatus tendon resection models

Abstract: Abstract Background: The role of altered joint mechanics on cartilage degeneration in in vivo models has not been studied successfully due to a lack of pre-injury information. We aimed 1) to develop an accurate in vivo canine model to measure the changes in joint loading and T2 star (T2*) relaxation time before and after unilateral supraspinatus tendon resections, and 2) to find the relationshi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the instance of T2 Ã relaxometry, our findings are consistent with Lee et al findings; in their study also they also found that larger T2 Ã values corresponded to increased cartilage degradation in a canine model. 26 However, in a research by Mankin et al, T2 Ã values declined as cartilage deterioration progressed. 27 Even though the cause of these findings is unknown, it may be possible due to signal averaging, in which the effects of cartilage matrix degradation that promote T2 Ã decay are counteracted by including fluid, such as an increase in cartilage water content or the inclusion of extracellular fluid in cartilage fissures, in the T2 Ã relaxation calculation.…”
Section: Discussionmentioning
confidence: 93%
“…In the instance of T2 Ã relaxometry, our findings are consistent with Lee et al findings; in their study also they also found that larger T2 Ã values corresponded to increased cartilage degradation in a canine model. 26 However, in a research by Mankin et al, T2 Ã values declined as cartilage deterioration progressed. 27 Even though the cause of these findings is unknown, it may be possible due to signal averaging, in which the effects of cartilage matrix degradation that promote T2 Ã decay are counteracted by including fluid, such as an increase in cartilage water content or the inclusion of extracellular fluid in cartilage fissures, in the T2 Ã relaxation calculation.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the high variability and poor reliability of delineating the medial margin of the rotator cuff insertion based on CT images, 10,39 the MR images were used to reconstruct this soft tissue insertion. To combine the CT and MR images, the medial margin of the rotator cuff insertion segmented from the MR images was transferred to the CT-based coordinates based on the transformation matrix, which was achieved from the bestfit alignment 20 of the CT-based and MR-based humerus models in the Geomagic software (Geomagic) (Figure 2A). Image registration.…”
Section: Exercise Testingmentioning
confidence: 99%
“…1 Transection of the supraspinatus tendon can lead to increased adduction and lateral shoulder subluxation without substan-tial abduction, as well as changes in articular cartilage contact strain that are associated with corresponding changes in the T2 Ã relaxation time. 2 As dogs disproportionately transfer more body weight to the thoracic limb musculature, trauma to the supraspinatus is of interest, in that injury may be anticipated to cause substantial lameness.…”
Section: Introductionmentioning
confidence: 99%